Maximizing the Characteristics of Qualitative Financial Statements of MSMEs in Bantul Regency - Nusron, Lulu Amalia; Clara Annisa Hendrawati Putri; Dekeng Setyo Budiarto (UNIB Press, 2025)
This study investigates the influence of human resource competence, the utilization of accounting information systems, and the implementation of SAK EMKM on the qualitative characteristics of financial statements among micro, small, and medium enterprises (MSMEs) in Bantul Regency, Indonesia. A quantitative approach was adopted, utilizing primary data collected from 120 MSME owners and operators through an online questionnaire distributed via Google Forms. Respondents were selected using purposive sampling. The data were analyzed using descriptive statistics, validity and reliability testing, and multiple linear regression analysis with the aid of SPSS version 25. The results reveal that human resource competence, accounting information systems, and the implementation of SAK EMKM significantly and positively impact the qualitative characteristics of MSME financial statements. These findings emphasize the critical role of improving human resource capabilities, leveraging accounting information systems, and applying relevant financial reporting standards to enhance the quality of financial reporting in the MSME sector.